Optimization of Gobak Sodor Based Neuroscience Learning Game as Character Education in Intellectual Disabilities - Ida Ayu Dian Pramantik (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
The purpose of writing this article is to find out the optimization of traditional gobak sodor neuroscience learning-based game activities as character education in intellectual disability with grade medium (ATG). Referring to the problems, most schools do not have policies and administrations regarding character education, most schools that have an environment that supports the implementation of character education, most teachers do not have good knowledge and attitude in character education, most teachers do not have good competence, most schools have used the curriculum and most teachers have not used assessments that are suitable for children. Character education and most of the community has not supported the course of character education. The purpose of writing this article is to find out the optimization of traditional